FAKTOR-FAKTOR YANG MEMPENGARUHI ALOKASI TENAGA KERJA KELUARGA PETANI KARET DI KABUPATEN MUARA ENIM SUMATERA SELATAN THE AFFECTING FAKTORS OF ALOCATION OF LABOR HOUSEHOLD FARMER IN MUARA ENIM SOUTH SUMATRA - Tirta Jaya Jenahar (Jurnal Media Wahana Ekonomika, 2013)
The research aims to find out the affecting factors of allocation of labour household farmer. Primary data are from sample traditional farmers and modern farmers at September until Nopember 2013. The sample size is 60 respondent household farmers in the district Muara Enim South Sumatra. The data analysed by regression analysis.The result showed the affect factors of allocation of labour are positive affect to income farmer, farmer age, total of member household, formal education, rubber replanting and negative affect to productivity of rubber, saving household, replanting are. Keyword : Analysis regretion , allocation of labour, impact